The biological clock keeps ticking, but exercise may turn it back - Andrea Deslandes (Arquivos de Neuro-Psiquiatria)
Aging is an inevitable process that is associated to loss of functional capacities in several body systems, like the cardiovascular, the skeletal muscle mass, the osteoarticular and the neuro-immune-endocrine systems. Changes appear due to interactions between genetic factors and way of life, such as diet and sedentary life style. This review shows evidence from the past twenty years concerning the importance of physical exercise to reduce the deleterious effects of aging, regarding the improvement in functional performance, the prevention of diseases and increased longevity. Moreover, physical exercise improves the cognitive function and the mood. Aerobic and strength training collaborate with the prevention and treatment of mental diseases, which are mostly prevalent in older adults, like major depression, dementia and Parkinson’s disease. Several mechanisms of neurobiological action are proposed to explain how exercise can actually reduce the effects of aging.